Repensando o Estado do Amapá (Brasil): entre (re)formatações e (re)configurações espaciais - Jadson Porto (Confins)
The State of Amapá (Brazil) had its spatiality institutionalized in 1943 when it was created as a Federal Territory. Stimulated by the guiding question of the investigations I have carried out for 25 years (what is Amapá?), I noticed that the spatial and territorial (re)formations of Amapá have been observed as a participant in the world-system since the 17th century by behaving as an integrant of territorial expansionist actions; a part involved in commercial interests; an inserted part in geopolitical and geoeconomic articulations; an articulate part of international interests; and a part constructed by national public policies. This work assumes that the space in Amapá is the result of external, articulate, and activated interests, and it is a reflection of belated political, economic, and institutional actions. For the ideas woven herein, the approaches of David Harvey, in Uneven Geographical Development, and Milton Santos, in systems of objects, norms, actions, economic circuits (upper and lower) and use of the territory, were adopted. The article is composed as follows: in the first section, I make brief considerations about uneven geographic development, (de)construction of space, and use of territory; in the second, I present another rethinking of the spatiality of Amapá; finally, the final considerations.